A high performance composite sealing gasket and preparation method thereof

After mixing nitrile rubber, ethylene propylene ternary rubber, anti-aging enhanced modified composite particles and modified epoxy resin composition, the sealing gasket was prepared by a two-stage vulcanization process, which solved the cracks and aging failure problems of the sealing gasket, extended the service life and improved the performance.

CN118374036BActive Publication Date: 2025-04-04WUXI XIXI CHEM MASCH PARTS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410646583.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-04-04
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

Existing sealing gaskets are prone to cracks and aging failure during use, resulting in reduced sealing performance and shortened service life.

Method used

A high-performance composite sealing gasket is used to prepare a high-performance composite sealing gasket. After mixing nitrile rubber, ethylene propylene tereum rubber, anti-aging reinforced modified composite particles and modified epoxy resin composition, it is intensively refined, refined and molded, and finally a two-stage vulcanization process is used to prepare the sealing gasket.

Benefits of technology

This method effectively solves the cracks and aging failure problems of the sealing gasket, extends the service life, and improves the mechanical properties, corrosion resistance, wear resistance and heat resistance of the sealing gasket.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118374036B_ABST
    Figure CN118374036B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-performance composite sealing gasket and a preparation method thereof, which comprises the following steps: S1, adding nitrile rubber, EPDM rubber, anti-aging enhanced modified composite particles, and modified epoxy resin composition into an internal mixer, mixing under heating, then adding talcum powder, zinc oxide, and paraffin, heating, mixing, and obtaining a mixed rubber material; S2, adding the mixed rubber material, sulfur, and a vulcanization accelerator into an open mixer, mixing, discharging, and obtaining a gasket rubber material; S3, molding, and obtaining a raw rubber gasket; S4, vulcanizing by a two-stage vulcanization process, and obtaining a sealing gasket. In the present invention, the anti-aging enhanced modified composite particles can give the sealing gasket system excellent anti-aging performance, and have long-term and temperature control properties, which can extend its service life. In addition, the mechanical properties, corrosion resistance, wear resistance, and heat resistance of the sealing gasket can be improved, and it has a multi-effect enhancement function, which can improve the comprehensive performance of the gasket.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sealing materials, and in particular to a high-performance composite sealing gasket and a preparation method thereof. Background Art

[0002] Sealing gaskets are widely used in the sealing of various equipment in modern industry. According to the material, they can be divided into metal sealing gaskets and non-metallic sealing gaskets. Non-metallic sealing gaskets and rubber gaskets are widely used, with excellent sealing performance, good wear resistance and chemical resistance, such as the polytetrafluoroethylene sealing gasket and its preparation method disclosed in patent CN116731458B, a puncture-resistant rubber material and sealing gasket disclosed in patent CN113429687B, and a method for preparing an oil-resistant rubber gasket and a high-strength oil-resistant rubber expansion joint disclosed in patent CN115558175A.

[0003] During the use of gaskets, cracks may appear due to the influence of external forces or insufficient strength. Cracks are divided into two forms: surface cracks and internal cracks. Surface cracks may cause leakage and rupture, while internal cracks may reduce the performance of the gasket and affect the sealing effect.

[0004] After long-term use, gaskets will lose their performance due to material aging, which manifests as deformation, hardening, loss of elasticity, etc. This failure form is usually related to factors such as gasket materials and usage environment. Rubber oxidation aging is a common way for rubber products to age, and its main cause is the effect of oxygen. When rubber products come into contact with oxygen, the double bonds in the rubber will be oxidized by oxygen to produce free radicals, which then continue to react with oxygen, resulting in the breakage of the rubber molecular chain, oxidation damage and aging.

[0005] Therefore, both crack failure and aging failure will seriously shorten the service life of the sealing gasket, and a reliable solution that can effectively solve this problem is urgently needed. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a high-performance composite sealing gasket and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high-performance composite sealing gasket, comprising the following steps:

[0008] S1, adding nitrile rubber, EPDM rubber, anti-aging enhanced modified composite particles, and modified epoxy resin composition into an internal mixer, mixing under heating, and then adding talcum powder, zinc oxide, and paraffin, heating, mixing, and obtaining a mixed rubber material;

[0009] S2, adding the mixed rubber material, sulfur and vulcanization accelerator into an open mill, mixing and discharging to obtain a gasket rubber material;

[0010] S3, molding the gasket rubber material to obtain a raw rubber gasket;

[0011] S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket to obtain a sealing gasket.

[0012] Preferably, the method for preparing the high-performance composite sealing gasket comprises the following steps:

[0013] S1. By weight, 100 parts of nitrile rubber, 13.5-54 parts of EPDM rubber, 7-28 parts of anti-aging enhanced modified composite particles, and 15.5-42 parts of modified epoxy resin composition are added to an internal mixer, mixed at 60-78° C. for 2-15 min, and then 4.5-19 parts of talc, 0.6-2.4 parts of zinc oxide, and 1.5-6 parts of paraffin are added, the temperature is raised to 80-85° C., and mixed for 4-16 min to obtain a mixed rubber material;

[0014] S2, adding 0.35-1.4 parts by weight of sulfur, 0.9-3.6 parts by weight of vulcanization accelerator and the mixed rubber material obtained in step S1 into an open mill, mixing at 65-75° C. for 4-15 minutes, and discharging to obtain a gasket rubber material;

[0015] S3, placing the gasket rubber material in a mold for compression molding according to the designed size and shape of the sealing gasket to obtain a raw rubber gasket;

[0016] S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket in a vulcanizer to obtain a sealing gasket; wherein, the first stage vulcanization temperature is 160-175°C, the vulcanization time is 5-15min, and the vulcanization pressure is 12-20MPa; the second stage vulcanization temperature is 150-160°C, the vulcanization time is 10-30min, and the vulcanization pressure is 5-15MPa.

[0017] Preferably, the anti-aging enhanced modified composite particles are prepared by the following method:

[0018] 1) A one-pot hydrothermal method was used to in situ modify reduced carbon dots on mesoporous silica to obtain anti-aging particles;

[0019] 2) preparing modified multi-walled carbon nanotubes;

[0020] 3) preparing modified carbon fiber;

[0021] 4) Grafting the modified multi-walled carbon nanotubes, anti-aging particles and modified carbon fibers to prepare composite functional particles;

[0022] 5) Modifying polystyrene on the composite functional particles to obtain polymer modified composite particles, and then immersing them in an antioxidant solution to obtain anti-aging enhanced modified composite particles.

[0023] Preferably, step 1) is specifically:

[0024] 1.25-5.0 g of mesoporous silica is added to 100-400 mL of an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 15-60 min. Then, 0.35-1.4 g of glucose, 0.15-0.6 g of oxalic acid, 0.25-1.1 g of lutein, and 0.12-0.48 g of 3-aminophenylboric acid are added, and ultrasonically dispersed for 0.5-2 h. The resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 165-190 ° C for 4-12 h, cooled to room temperature and centrifuged, washed with ethanol, and vacuum dried at 50-70 ° C for 6-24 h to obtain anti-aging particles.

[0025] Preferably, step 2) is specifically:

[0026] Take 1.5-6g of multi-walled carbon nanotubes and add them into a mixed acid consisting of 60-240mL of 95% by mass concentrated sulfuric acid and 80mL of 60% by mass concentrated nitric acid, stir and reflux at 70-90°C for 6-24h, cool to room temperature, centrifuge and filter, wash the solid product with deionized water until neutral, and vacuum dry at 50-65°C for 6-24h to obtain modified multi-walled carbon nanotubes.

[0027] Preferably, step 3) is specifically:

[0028] The carbon fiber is added to ethanol and soaked for 1-4 hours, filtered, and dried at 90-110°C to constant weight to obtain pretreated carbon fiber; 2.5-10g of the pretreated carbon fiber is added to 125-500mL of a mixed acid solution consisting of 15% by mass hydrogen peroxide and 55% by mass sulfuric acid, ultrasonically dispersed for 15-60min, heated to 80-95°C, treated under a 300-400W microwave for 15-45min, cooled to room temperature, filtered, washed with deionized water until neutral, and dried at 90-110°C to constant weight to obtain modified carbon fiber;

[0029] The carbon fiber is micron-sized short-cut carbon fiber with a length of 50 to 400 μm.

[0030] Preferably, step 4) is specifically:

[0031] 4-16g of modified carbon fiber, 1.9-7.6g of anti-aging particles, 0.75-3.0g of modified multi-walled carbon nanotubes, and 2.0-8.5g of Mn(NO3)2 were added to 150-600mL of an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 0.5-2h. The resulting dispersion was transferred to a reactor and reacted at 220-280°C for 2-8h. After the reaction was completed, it was cooled to room temperature, centrifuged and filtered, the solid product was washed with deionized water, and then vacuum dried at 60-80°C for 4-12h to obtain composite functional particles.

[0032] Preferably, step 5) is specifically:

[0033] 5-1. Wash the styrene monomer 2-6 times with a 0.1-0.4 mol / L NaOH solution, then wash with deionized water until neutral, and then dry with anhydrous Na2SO4 to obtain purified styrene monomer;

[0034] 5-2. Take 1-4g of composite functional particles and 0.1-0.4mL of silane coupling agent KH-570 and add them to 25-100mL of isopropanol, stir at 50-75°C for 1-4h, filter, wash the solid product with isopropanol, then add it to 35-150mL of purified styrene monomer, stir and disperse for 30-90min to obtain a precursor solution;

[0035] 5-3. Take 0.75-3.0g of sodium dodecyl sulfate and add it to 200-400mL of deionized water. After stirring for 2-15min, add 0.14-0.56g of hexadecanol and stir at 40-60°C for 5-30min to obtain an additive solution.

[0036] 5-4. Add the precursor liquid to the auxiliary liquid, stir for 15-60 minutes, then heat to 62-73°C, drop 0.25-1.2g of azobisisobutyronitrile, and react at constant temperature for 2.5-8 hours to obtain polymer-modified composite particles;

[0037] 5-5. Add 0.5-2 g of polymer modified composite particles to an antioxidant solution with a concentration of 1-10 mg / mL, first ultrasonicate for 0.5-2 h, then soak for 3-10 h, centrifuge, wash the solid product with ethanol, and vacuum dry at 40-60° C. for 4-12 h to obtain anti-aging enhanced modified composite particles;

[0038] The antioxidant solution is prepared by adding any one of antioxidant D, antioxidant RD, antioxidant 124 and antioxidant MB into acetone.

[0039] Preferably, the modified epoxy resin composition is prepared by the following method:

[0040] Add 2.25-9 g of 2,2'-diaminodiphenyl disulfide to 20-80 g of ethanol, stir at 40-55°C for 5-30 min, then add 12.5-50 g of bisphenol F epoxy resin and 5-20 g of bis(4-epoxypropoxy)diphenyl disulfide, stir at 60-80°C for 15-60 min, then place in a vacuum oven, degas at 50-65°C for 15-60 min, finally keep warm at 120-140°C for 2-6 h, cool to room temperature, and obtain a self-healing epoxy resin.

[0041] The present invention also provides a high-performance composite sealing gasket, which is prepared by the method as described above.

[0042] The beneficial effects of the present invention are:

[0043] The present invention provides a high-performance composite sealing gasket and a preparation method thereof. The sealing gasket of the present invention can effectively solve the problems of crack failure and aging failure. In the present invention, the anti-aging enhanced modified composite particles can give the sealing gasket system excellent anti-aging performance, and have long-term effectiveness and temperature control (adaptive enhancement of anti-aging performance at high temperature), which can extend its service life. In addition, the mechanical properties, corrosion resistance, wear resistance and heat resistance of the sealing gasket can be improved, and it has a multi-effect enhancement function, which can improve the comprehensive performance of the gasket.

[0044] In the present invention, the disulfide bond introduced into the modified epoxy resin composition can give the system good self-repairing performance, and the anti-aging enhanced modified composite particles have a promoting effect on the self-repairing performance, and the two can have a synergistic enhancement effect; in addition, the modified epoxy resin composition can further improve the strength and chemical resistance of the system;

[0045] In the anti-aging particles of the present invention, the surface of mesoporous silica is rich in silanol groups, and the surface of carbon dots is rich in functional groups such as carboxyl groups, amino groups, and hydroxyl groups. These groups can bind to Mn through electrostatic adsorption and / or coordination. 2+ Combined, the same Mn 2+ It can also combine with the carboxyl groups on the surface of modified multi-walled carbon nanotubes and modified carbon fibers, so that the modified multi-walled carbon nanotubes and anti-aging particles can be grafted onto the modified carbon fibers in large quantities and evenly. After high-temperature hydrothermal reaction, Mn 2+ MnO2 is formed, and grafting is achieved through stable metal oxide bonds. A network structure with anti-aging particles loaded with MnO2 as connecting nodes is formed between the modified multi-walled carbon nanotubes and the modified carbon fibers, thereby significantly enhancing the improvement effect of the modified multi-walled carbon nanotubes and the modified carbon fibers on the mechanical properties and thermal conductivity of the system;

[0046] In the present invention, the coating effect of polystyrene can increase the compatibility between the composite functional particles and the organic system, so that the entire composite functional particles can be evenly dispersed in the sealing gasket system, and the dragging and entrainment effect provided by the anti-aging particles loaded with MnO2 as the connecting nodes of the network structure enables the reinforced network structure formed by the modified multi-walled carbon nanotubes and the modified carbon fibers to be dispersed in the system, which is beneficial to the performance enhancement; on the other hand, polystyrene has a certain heat resistance temperature (it will gradually melt at a temperature of 150-200°C), and can protect the carbon dots grafted on the mesoporous silica during the vulcanization process in the preparation of the sealing gasket and the subsequent storage and transportation process, thereby reducing the failure rate;

[0047] When used in a non-high temperature environment (the temperature environment is not enough to melt a large amount of the polystyrene coating), the structural system of the modified multi-walled carbon nanotubes loaded with antioxidants provides the main antioxidant function, and the loading effect of the modified multi-walled carbon nanotubes provides a sustained release effect, which can slowly and long-term provide antioxidants, thereby providing long-term antioxidant ability; of course, since the polystyrene coating is not airtight or 100% coated, and the polystyrene coating will also be subject to certain degradation during the subsequent preparation, storage, transportation and use, the structural system of the mesoporous silica loaded with carbon dots will also assist in providing partial antioxidant function during non-high temperature use; some oxygen free radicals entering the system can also be captured and removed by the carbon dots grafted on the mesoporous silica.

[0048] When used at high temperatures (e.g., 165-200°C), the effects of thermal oxidation aging will bring greater challenges to the sealing gasket system. At this time, the polystyrene coating will accelerate melting, exposing more carbon dots inside, so that a larger number of oxygen free radicals can be captured and removed, thereby adaptively improving its thermal oxidation resistance. In this process, the speed at which the modified multi-walled carbon nanotubes release antioxidants will also be improved to a certain extent. Therefore, in the anti-aging enhanced modified composite particle structure system of the present invention, the structure of polystyrene, carbon dot-loaded mesoporous silica and the structure of multi-walled carbon nanotubes loaded with antioxidants contribute to the anti-aging performance in a coordinated and complementary manner. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 is the infrared absorption spectrum of the anti-aging particles (SiO2@RCDs) prepared in Example 4;

[0050] Figure 2 The test results of the antioxidant properties of the anti-aging particles (SiO2@RCDs) prepared in Example 4;

[0051] Figure 3The sustained release performance test results of the anti-aging enhanced modified composite particles (PS@SiO2@RCDs-CF-CNTs@RD) prepared in Example 4;

[0052] Figure 4 The tensile strength test results of the embodiments and comparative examples are shown in FIG.

[0053] Figure 5 The following are the test results of the resilience of the embodiments and comparative examples;

[0054] Figure 6 The following are the test results of the room temperature self-repairing performance of the embodiments and comparative examples;

[0055] Figure 7 The self-healing performance test results at 120°C of the embodiment and the comparative example;

[0056] Figure 8 The sealing performance test results of the embodiments and comparative examples are shown in FIG.

[0057] Fig. 9 The figures are the test results of the anti-aging performance of the embodiments and comparative examples. DETAILED DESCRIPTION

[0058] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0059] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0060] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0061] The present invention provides a high-performance composite sealing gasket and a preparation method thereof, the method comprising the following steps:

[0062] S1. By weight, 100 parts of nitrile rubber, 13.5-54 parts of EPDM rubber, 7-28 parts of anti-aging enhanced modified composite particles, and 15.5-42 parts of modified epoxy resin composition are added to an internal mixer, mixed at 60-78° C. for 2-15 min, and then 4.5-19 parts of talc, 0.6-2.4 parts of zinc oxide, and 1.5-6 parts of paraffin are added, the temperature is raised to 80-85° C., and mixed for 4-16 min to obtain a mixed rubber material;

[0063] S2, adding 0.35-1.4 parts by weight of sulfur, 0.9-3.6 parts by weight of vulcanization accelerator and the mixed rubber material obtained in step S1 into an open mill, mixing at 65-75° C. for 4-15 minutes, and discharging to obtain a gasket rubber material;

[0064] S3, placing the gasket rubber material in a mold for compression molding according to the designed size and shape of the sealing gasket to obtain a raw rubber gasket;

[0065] S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket in a vulcanizer to obtain a sealing gasket; wherein, the first stage vulcanization temperature is 160-175°C, the vulcanization time is 5-15min, and the vulcanization pressure is 12-20MPa; the second stage vulcanization temperature is 150-160°C, the vulcanization time is 10-30min, and the vulcanization pressure is 5-15MPa.

[0066] In a preferred embodiment, the vulcanization accelerator is the vulcanization accelerator TMTD.

[0067] In the present invention, the anti-aging enhanced modified composite particles are prepared by the following method:

[0068] 1) In-situ modification of reduced carbon dots on mesoporous silica using a one-pot hydrothermal method to obtain anti-aging particles:

[0069] 1.25-5.0 g of mesoporous silica is added to 100-400 mL of an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 15-60 min. Then, 0.35-1.4 g of glucose, 0.15-0.6 g of oxalic acid, 0.25-1.1 g of lutein, and 0.12-0.48 g of 3-aminophenylboric acid are added, and ultrasonically dispersed for 0.5-2 h. The resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 165-190 ° C for 4-12 h, cooled to room temperature and centrifuged, washed with ethanol, and vacuum dried at 50-70 ° C for 6-24 h to obtain anti-aging particles.

[0070] Mesoporous silica can be commercially available or prepared by conventional methods, such as the following literature: Sheng Weichen, Zhao Wenfeng, Shu Zhiping, et al. Research on the preparation and application of mesoporous nano-silica [C] / / National Conference on Coatings Science and Technology. China Materials Research Society; Shanghai Chemical Society, 2008.

[0071] 2) Preparation of modified multi-walled carbon nanotubes:

[0072] Take 1.5-6g of multi-walled carbon nanotubes and add them into a mixed acid consisting of 60-240mL of 95% by mass concentrated sulfuric acid and 80mL of 60% by mass concentrated nitric acid, stir and reflux at 70-90°C for 6-24h, cool to room temperature, centrifuge and filter, wash the solid product with deionized water until neutral, and vacuum dry at 50-65°C for 6-24h to obtain modified multi-walled carbon nanotubes.

[0073] 3) Preparation of modified carbon fiber:

[0074] The carbon fiber is added to ethanol and soaked for 1-4 hours, filtered, and dried at 90-110°C to constant weight to obtain pretreated carbon fiber; 2.5-10g of the pretreated carbon fiber is added to 125-500mL of a mixed acid solution consisting of 15% by mass hydrogen peroxide and 55% by mass sulfuric acid, ultrasonically dispersed for 15-60min, heated to 80-95°C, treated under a 300-400W microwave for 15-45min, cooled to room temperature, filtered, washed with deionized water until neutral, and dried at 90-110°C to constant weight to obtain modified carbon fiber;

[0075] The carbon fiber is micron-sized short-cut carbon fiber with a length of 50 to 400 μm.

[0076] 4) Using the metal ion bridging effect, the modified multi-walled carbon nanotubes, anti-aging particles and modified carbon fibers are grafted to prepare composite functional particles:

[0077] 4-16g of modified carbon fiber, 1.9-7.6g of anti-aging particles, 0.75-3.0g of modified multi-walled carbon nanotubes, and 2.0-8.5g of Mn(NO3)2 were added to 150-600mL of an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 0.5-2h. The resulting dispersion was transferred to a reactor and reacted at 220-280°C for 2-8h. After the reaction was completed, it was cooled to room temperature, centrifuged and filtered, the solid product was washed with deionized water, and then vacuum dried at 60-80°C for 4-12h to obtain composite functional particles.

[0078] 5) Modifying polystyrene on the composite functional particles to obtain polymer modified composite particles, and then immersing them in an antioxidant solution to obtain anti-aging enhanced modified composite particles, the specific steps are:

[0079] 5-1. Wash the styrene monomer 2-6 times with a 0.1-0.4 mol / L NaOH solution, then wash with deionized water until neutral, and then dry with anhydrous Na2SO4 to obtain purified styrene monomer;

[0080] 5-2. Take 1-4g of composite functional particles and 0.1-0.4mL of silane coupling agent KH-570 and add them to 25-100mL of isopropanol, stir at 50-75°C for 1-4h, filter, wash the solid product with isopropanol, then add it to 35-150mL of purified styrene monomer, stir and disperse for 30-90min to obtain a precursor solution;

[0081] 5-3. Take 0.75-3.0g of sodium dodecyl sulfate and add it to 200-400mL of deionized water. After stirring for 2-15min, add 0.14-0.56g of hexadecanol and stir at 40-60°C for 5-30min to obtain an additive solution.

[0082] 5-4. Add the precursor liquid to the auxiliary liquid, stir for 15-60 minutes, then heat to 62-73°C, drop 0.25-1.2g of azobisisobutyronitrile, and react at constant temperature for 2.5-8 hours to obtain polymer-modified composite particles;

[0083] 5-5. Add 0.5-2 g of polymer modified composite particles to an antioxidant solution with a concentration of 1-10 mg / mL, first ultrasonicate for 0.5-2 h, then soak for 3-10 h, centrifuge, wash the solid product with ethanol, and vacuum dry at 40-60° C. for 4-12 h to obtain anti-aging enhanced modified composite particles;

[0084] The antioxidant solution is prepared by adding any one of antioxidant D, antioxidant RD, antioxidant 124 and antioxidant MB into acetone. In a preferred embodiment, the antioxidant is antioxidant RD.

[0085] In the present invention, the modified epoxy resin composition is prepared by the following method:

[0086] Add 2.25-9 g of 2,2'-diaminodiphenyl disulfide to 20-80 g of ethanol, stir at 40-55°C for 5-30 min, then add 12.5-50 g of bisphenol F epoxy resin and 5-20 g of bis(4-epoxypropoxy)diphenyl disulfide, stir at 60-80°C for 15-60 min, then place in a vacuum oven, degas at 50-65°C for 15-60 min, finally keep warm at 120-140°C for 2-6 h, cool to room temperature, and obtain a self-healing epoxy resin.

[0087] Mechanism analysis and explanation:

[0088] In the present invention, the anti-aging enhanced modified composite particles can give the sealing gasket system excellent anti-aging performance, and have long-term effectiveness and temperature control (anti-aging performance is adaptively enhanced at high temperature), which can extend its service life. In addition, it can also improve the mechanical properties, corrosion resistance, wear resistance and heat resistance of the sealing gasket, and has a multi-effect enhancement function, which can improve the comprehensive performance of the gasket;

[0089] In the present invention, the disulfide bonds introduced into the modified epoxy resin composition can give the system good self-repairing properties, and the anti-aging enhanced modified composite particles have a promoting effect on the self-repairing properties, and the two can have a synergistic enhancement effect; in addition, the modified epoxy resin composition can further improve the strength and chemical resistance of the system.

[0090] For sealing gaskets, the improvement of mechanical strength, wear resistance and aging resistance can effectively reduce the probability of wear failure, aging failure and other situations, thereby improving the use effect of sealing gaskets and extending their service life. The role of self-repairing performance is mainly that when cracks / cracks appear on the sealing gasket due to the use environment, stress and other effects, the cracks / cracks can be repaired with the help of the self-repairing function provided by the modified epoxy resin composition, thereby greatly reducing the occurrence of crack failure, thereby giving the sealing gasket a long-term anti-leakage function.

[0091] Organic degradation caused by oxidizing substances is one of the main factors for aging failure of sealing gaskets, especially in high temperature environments, where thermal oxidation will aggravate the degradation of organic matter. In the present invention, the sealing gasket system is endowed with excellent anti-aging properties by anti-aging enhanced modified composite particles, which can effectively solve this problem and thus extend the service life.

[0092] The main mechanism of the present invention is described in detail below in combination with a specific preparation method to facilitate understanding of the present invention. 1. Main mechanism of anti-aging enhanced modified composite particles:

[0093] 1) The present invention firstly adopts a one-pot hydrothermal method to in-situ modify reduced carbon dots on mesoporous silica to obtain anti-aging particles, which are denoted as SiO2@RCDs:

[0094] Mesoporous silica has a rich pore structure and a large specific surface area, which is conducive to the grafting of a large number of carbon dots on its surface and in the mesopores; the carbon dots of the present invention use glucose, oxalic acid and lutein as carbon sources, 3-aminophenylboronic acid as boron source and nitrogen source, and synthesize boron-nitrogen doped reduced carbon dots through a one-pot hydrothermal method; lutein has natural antioxidant properties, and the prepared carbon dots well inherit the reducing property of lutein and show excellent antioxidant capacity; boron doping can affect the electron density distribution, increase the electron transfer rate, and enhance the reducing property of the carbon dots; the surface of the reduced carbon dots has abundant amino, carboxyl, hydroxyl and other functional groups;

[0095] Mesoporous silica acts as a load on carbon dots, which helps to keep the carbon dots stably dispersed and reduce their agglomeration. At the same time, its mesoporous structure can also provide a long-lasting sustained-release effect. After being added to the sealing gasket system, the oxygen free radicals entering the system can be captured and removed by the carbon dots. The role of the mesoporous structure load can keep the carbon dots stable for a long time, avoiding their migration and failure, thereby exerting a long-lasting antioxidant effect.

[0096] 2) Then, a modified multi-walled carbon nanotube with rich surface carboxyl groups was prepared by strong acid treatment, and a modified carbon fiber with rich surface carboxyl groups was prepared by mixed acid combined with microwave treatment;

[0097] Multi-walled carbon nanotubes can improve the mechanical properties, corrosion resistance and heat resistance of the rubber system, and they have good thermal conductivity, making the heat distribution more uniform, which can promote vulcanization (Liu Zhuoxin, Liu Meihong, Li Yuxian, et al. Multi-walled carbon nanotubes enhance the aging resistance of asbestos-free gaskets [J]. Lubrication and Sealing, 2023, 48(6): 175-179.); However, the main drawback of multi-walled carbon nanotubes is that they are difficult to disperse in organic systems.

[0098] Carbon fiber is a commonly used inorganic fiber filler for sealing materials, which can significantly improve the wear resistance, mechanical strength and heat and corrosion resistance of sealing materials, but it also has the problem of being difficult to disperse in organic systems. In the present invention, carboxyl groups are introduced through modification treatment to enhance the wettability of multi-walled carbon nanotubes and carbon fibers in organic systems, and the above problems can be solved by further constructing anti-aging enhanced modified composite particles with special structures, which will be described in detail below.

[0099] 3) Then through the metal ion Mn 2+ The modified multi-walled carbon nanotubes, anti-aging particles and modified carbon fibers were grafted by the bridging effect to obtain composite functional particles, which were recorded as SiO2@RCDs-CF-CNTs.

[0100] In the anti-aging particles, the surface of mesoporous silica is rich in silanol groups, and the surface of carbon dots is rich in functional groups such as carboxyl, amino, and hydroxyl groups. These groups can interact with Mn through electrostatic adsorption and / or coordination. 2+ Combined, the same Mn 2+ It can also combine with the carboxyl groups on the surface of modified multi-walled carbon nanotubes and modified carbon fibers, so that the modified multi-walled carbon nanotubes and anti-aging particles can be grafted onto the modified carbon fibers in large quantities and evenly. After high-temperature hydrothermal reaction, Mn 2+MnO2 is formed, and grafting is achieved through stable metal oxide bonds. A network structure with anti-aging particles loaded with MnO2 as connecting nodes is formed between the modified multi-walled carbon nanotubes and the modified carbon fibers, thereby significantly enhancing the effect of the modified multi-walled carbon nanotubes and modified carbon fibers on improving the mechanical properties and thermal conductivity of the system.

[0101] 4) Then, polystyrene is modified on the composite functional particles to obtain polymer modified composite particles, and finally, the particles are immersed in an antioxidant solution to obtain anti-aging enhanced modified composite particles, which are recorded as PS@SiO2@RCDs-CF-CNTs@RD:

[0102] In the composite functional particles, the surface of mesoporous silica is rich in silanol groups, which can react with the silane coupling agent KH-570, so that the silane coupling agent KH-570 is modified on the surface of the mesoporous silica. At the same time, KH-570 has unsaturated olefin double bonds and can participate in the copolymerization of styrene. Therefore, through the bridging effect of KH-570, polystyrene can be mainly grafted and coated on the surface of the mesoporous silica; of course, a small amount of polystyrene will also be grafted onto the modified multi-walled carbon nanotubes and modified carbon fibers; then, through the impregnation method, the nanotube cavity structure of the modified multi-walled carbon nanotubes is used to load the antioxidant to obtain anti-aging enhanced modified composite particles.

[0103] On the one hand, the coating effect of polystyrene can increase the compatibility between the composite functional particles and the organic system, so that the entire composite functional particles can be evenly dispersed in the sealing gasket system, and the dragging and entrainment provided by the anti-aging particles loaded with MnO2 as the connecting nodes of the network structure enable the reinforced network structure formed by the modified multi-walled carbon nanotubes and the modified carbon fibers to be dispersed in the system, which is beneficial to the performance enhancement; on the other hand, the polystyrene coating film prepared in the present invention has a certain heat resistance temperature (it will gradually melt at a temperature of 165-200°C), and can protect the carbon dots grafted on the mesoporous silica during the vulcanization process in the preparation of the sealing gasket and the subsequent storage and transportation process, thereby reducing the amount of failure. It should be understood that although the polystyrene coating film may partially melt during the vulcanization process, the vulcanization time is short, so the polystyrene coating film will not be excessively damaged during the vulcanization process.

[0104] When used in a non-high temperature environment (the temperature environment is not enough to melt a large amount of the polystyrene coating), the structural system of the modified multi-walled carbon nanotubes loaded with antioxidants provides the main antioxidant function, and the loading effect of the modified multi-walled carbon nanotubes provides a sustained release effect, which can slowly and long-term provide antioxidants, thereby providing long-term antioxidant ability; of course, since the polystyrene coating is not airtight or 100% coated, and the polystyrene coating will also be subject to certain degradation during the subsequent preparation, storage, transportation and use, the structural system of the mesoporous silica loaded with carbon dots will also assist in providing partial antioxidant function during non-high temperature use; some oxygen free radicals entering the system can also be captured and removed by the carbon dots grafted on the mesoporous silica.

[0105] When used at high temperatures (e.g., 165-200°C), the effect of thermal oxidation aging will bring greater challenges to the gasket system. At this time, the polystyrene coating will accelerate melting, exposing more carbon dots inside, so that a larger number of oxygen free radicals can be captured and removed, thereby adaptively improving its thermal oxidation resistance. In this process, the speed at which the modified multi-walled carbon nanotubes release antioxidants will also be improved to a certain extent. Therefore, in the anti-aging enhanced modified composite particle structure system of the present invention, the structure of polystyrene, carbon dot-loaded mesoporous silica and the structure of multi-walled carbon nanotubes loaded with antioxidants contribute to the anti-aging performance in a coordinated and complementary manner.

[0106] Therefore, the sealing gasket of the present invention can adapt to use in a certain high-temperature environment, and is particularly suitable for use in an environment with alternating high and low temperatures.

[0107] 2. The main mechanism of modified epoxy resin composition:

[0108] In the present invention, an epoxy resin with rich disulfide bonds is synthesized by using an epoxy monomer bis(4-glycidoxy)diphenyl disulfide with a disulfide bond and a curing agent 2,2'-diaminodiphenyl disulfide with a disulfide bond, and compounded with a bisphenol F epoxy resin to obtain a modified epoxy resin composition; the modified epoxy resin composition provides an excellent room temperature self-healing function by virtue of the characteristics of disulfide bond metathesis exchange, thereby improving the use effect and service life of the sealing gasket;

[0109] The mechanism of disulfide bonds is:

[0110] Disulfide bonds are usually formed by coupling two thiol groups. The bond energy of disulfide bonds is weaker than that of carbon-carbon single bonds and carbon-hydrogen bonds. In many molecular structures, disulfide bonds are usually weak bonds. The "bond" of disulfide bonds is not strong, so the connection between S atoms and S atoms is easy to break. However, the broken SS bond can be reconnected with other broken SS bonds to form a new SS covalent bond "bond", so it is called a dynamic disulfide bond. Introducing disulfide bonds into functional materials can make them have self-healing properties, which is mainly because disulfide bonds are reversible under certain conditions (Zhou Zhen, Su Xunzheng, Liu Jingcheng, et al. Research progress of intrinsic self-healing coatings prepared based on photochemical reactions [J]. Imaging Science and Photochemistry, 2020, 38(5): 10. DOI: 10.7517 / issn.1674-0475.200404.).

[0111] In addition, the anti-aging enhanced modified composite particles also have at least the following contributions to the self-repair function:

[0112] (1) Anti-aging enhancement The manganese dioxide in the modified composite particles has a catalytic effect on the disulfide bond exchange reaction (Mei Jinfeng. Synthesis and properties of autonomous self-healing materials based on dynamic non-covalent bonds [D]. Nanjing University [2024-04-25].), thereby improving the self-healing ability of the disulfide bond introduced into the epoxy resin. In addition, the sp 2 and sp 3 The hybrid carbon interface structure and the huge electron acceptor / donor function promote the electron transfer, which enhances the catalytic activity of manganese dioxide.

[0113] (2) The doping of B in the reduced carbon dots in the anti-aging enhanced modified composite particles enables a certain amount of dynamic BO bonds to be formed in the final particle system. The dynamic nature of the BO bonds makes it repairable (Li Qianqian. Conductive self-healing materials based on reversible boron-oxygen bond cross-linked terminal hydroxyl polybutadiene [D]. Hefei University of Technology [2024-04-25].), thereby enhancing the self-healing ability of the system on the other hand.

[0114] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0115] Reagent Source Description

[0116] Nitrile rubber, JSRN220S, Shanghai Yiyong New Material Technology Co., Ltd.;

[0117] Ethylene propylene diene monomer (EPDM), Dow 3720P, was purchased from Shanghai Beidaer New Materials Co., Ltd.;

[0118] Zinc oxide, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;

[0119] Paraffin Jiangsu Runfeng Synthetic Technology Co., Ltd.;

[0120] Talc, Jiangsu Runfeng Synthetic Technology Co., Ltd.;

[0121] Vulcanization accelerator TMTD, Shanghai Kaiyin Chemical Co., Ltd.;

[0122] Mesoporous silica, average particle size 80 nm, pore size 2.9 nm, model XFF11, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;

[0123] Multi-walled carbon nanotubes, average inner diameter: 30nm, average length: 8μm, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;

[0124] Micron-sized chopped carbon fiber, average diameter 8μm, average length 300μm, Changzhou Yaobang Friction Material Factory;

[0125] Styrene, AR, Jinan Mingbang Chemical Co., Ltd.;

[0126] Silane coupling agent KH-570, γ-(methacryloyloxy)propyltrimethoxysilane, Nanjing Pinyoudao Chemical Technology Co., Ltd.;

[0127] Antiaging agent RD, Nantong Runfeng Petrochemical Co., Ltd.;

[0128] Bisphenol F epoxy resin, brand: Senfida, model: EMTE160, purchased from Suzhou Senfida Chemical Co., Ltd.;

[0129] Bis(4-glycidoxy)diphenyl disulfide, namely 4,4'-bis(glycidoxy)diphenyl disulfide, Dalian Lianhua Chemical Co., Ltd.;

[0130] 2,2'-Diaminodiphenyl disulfide (AFD), Jiangsu Runfeng Synthetic Technology Co., Ltd.;

[0131] The other raw materials not mentioned are conventional commercially available products.

[0132] Example 1

[0133] A high-performance composite sealing gasket and a preparation method thereof, the method comprising the following steps:

[0134] S1. Weigh the following raw materials by weight:

[0135]

[0136] According to the above ratio, nitrile rubber, EPDM rubber, anti-aging enhanced modified composite particles, and modified epoxy resin composition were added into an internal mixer, mixed at 75° C. for 5 min, and then talcum powder, zinc oxide, and paraffin were added, the temperature was raised to 82° C., and mixed for 8 min to obtain a mixed rubber material;

[0137] S2. Add the mixed rubber material, sulfur and vulcanization accelerator into an open mixing mill, mix at 70°C for 8 minutes, and discharge the material to obtain a gasket rubber material; S3. Place the gasket rubber material in a mold for compression molding according to the designed size and shape of the sealing gasket to obtain a raw rubber gasket; S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket in a vulcanizer to obtain a sealing gasket; wherein, the first stage vulcanization temperature is 165°C, the vulcanization time is 10 minutes, and the vulcanization pressure is 18MPa; the second stage vulcanization temperature is 155°C, the vulcanization time is 20 minutes, and the vulcanization pressure is 14MPa; and a sealing gasket is obtained.

[0138] In this embodiment, the anti-aging enhanced modified composite particles are prepared by the following method:

[0139] 1) In-situ modification of reduced carbon dots on mesoporous silica using a one-pot hydrothermal method to obtain anti-aging particles:

[0140] 2.4 g of mesoporous silica was added to 200 mL of an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 30 min. Then, 0.7 g of glucose, 0.3 g of oxalic acid, 0.55 g of lutein, and 0.24 g of 3-aminophenylboric acid were added and ultrasonically dispersed for 1 h. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor, reacted at 175 ° C for 8 h, cooled to room temperature, and centrifuged and filtered. The solid product was washed with ethanol and vacuum dried at 55 ° C for 12 h to obtain anti-aging particles.

[0141] 2) Preparation of modified multi-walled carbon nanotubes:

[0142] Take 3 g of multi-walled carbon nanotubes and add them into a mixed acid consisting of 120 mL of 95% by mass concentrated sulfuric acid and 80 mL of 60% by mass concentrated nitric acid, stir and reflux at 80°C for 12 hours, cool to room temperature, centrifuge and filter, wash the solid product with deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain modified multi-walled carbon nanotubes.

[0143] 3) Preparation of modified carbon fiber:

[0144] The micron-sized short-cut carbon fiber was soaked in ethanol for 2 hours, filtered, and dried at 100°C to constant weight to obtain pretreated carbon fiber; 5 g of pretreated carbon fiber was added to 250 mL of a mixed acid solution consisting of 10% by mass hydrogen peroxide and 55% by mass sulfuric acid, ultrasonically dispersed for 30 minutes and then heated to 90°C, treated under a 350 W microwave for 30 minutes, cooled to room temperature and filtered, washed with deionized water until neutral, and dried at 100°C to constant weight to obtain modified carbon fiber.

[0145] 4) Using the metal ion bridging effect, the modified multi-walled carbon nanotubes, anti-aging particles and modified carbon fibers are grafted to prepare composite functional particles:

[0146] 8 g of modified carbon fiber, 3.8 g of anti-aging particles, 1.6 g of modified multi-walled carbon nanotubes, and 3.58 g of Mn(NO3)2 were added to 300 mL of ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 1 hour. The resulting dispersion was transferred to a reactor and reacted at 250°C for 4 hours. After the reaction was completed, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and then vacuum dried at 70°C for 8 hours to obtain composite functional particles.

[0147] 5) Modifying polystyrene on the composite functional particles to obtain polymer modified composite particles, and then immersing them in an antioxidant solution to obtain anti-aging enhanced modified composite particles, the specific steps are:

[0148] 5-1. Wash the styrene monomer three times with a 0.2 mol / L NaOH solution, then wash with deionized water until neutral, and then dry with anhydrous Na2SO4 to obtain purified styrene monomer;

[0149] 5-2. Take 2 g of composite functional particles and 2 mL of silane coupling agent KH-570 and add them to 50 mL of isopropanol. Stir at 65 °C for 2 h, filter, wash the solid product with isopropanol, then add it to 75 mL of purified styrene monomer, stir and disperse for 45 min to obtain a precursor solution.

[0150] 5-3. Take 1.5 g of sodium dodecyl sulfate and add it to 400 mL of deionized water. After stirring for 5 min, add 0.28 g of hexadecanol and stir at 50°C for 10 min to obtain an additive solution.

[0151] 5-4. Add the precursor solution 1 to the auxiliary solution, stir for 30 minutes, then heat to 68°C, drop 0.25g of azobisisobutyronitrile, and react at constant temperature for 5 hours to obtain polymer-modified composite particles;

[0152] 5-5. Add 1 g of polymer modified composite particles to an acetone solution of antioxidant RD at a concentration of 4 mg / mL, first ultrasonicate for 1 h, then soak for 6 h, centrifuge, wash the solid product with ethanol, and vacuum dry at 50°C for 8 h to obtain anti-aging enhanced modified composite particles.

[0153] In this embodiment, the modified epoxy resin composition is prepared by the following method:

[0154] 4.3 g of 2,2'-diaminodiphenyl disulfide was added to 40 g of ethanol, stirred at 50°C for 10 min, then 26.5 g of bisphenol F epoxy resin and 10 g of bis(4-epoxypropoxy)diphenyl disulfide were added, stirred at 70°C for 30 min, then placed in a vacuum oven, degassed at 60°C for 30 min, and finally kept at 130°C for 4 h, cooled to room temperature, and a self-healing epoxy resin was obtained.

[0155] Example 2

[0156] A high-performance composite sealing gasket and a preparation method thereof, the method comprising the following steps:

[0157] S1. Weigh the following raw materials by weight:

[0158]

[0159]

[0160] According to the above ratio, nitrile rubber, EPDM rubber, anti-aging enhanced modified composite particles, and modified epoxy resin composition were added into an internal mixer, mixed at 75° C. for 5 min, and then talcum powder, zinc oxide, and paraffin were added, the temperature was raised to 82° C., and mixed for 8 min to obtain a mixed rubber material;

[0161] S2. Add the mixed rubber material, sulfur and vulcanization accelerator into an open mixing mill, mix at 70°C for 8 minutes, and discharge the material to obtain a gasket rubber material; S3. Place the gasket rubber material in a mold for compression molding according to the designed size and shape of the sealing gasket to obtain a raw rubber gasket; S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket in a vulcanizer to obtain a sealing gasket; wherein, the first stage vulcanization temperature is 165°C, the vulcanization time is 10 minutes, and the vulcanization pressure is 18MPa; the second stage vulcanization temperature is 155°C, the vulcanization time is 20 minutes, and the vulcanization pressure is 14MPa; and a sealing gasket is obtained.

[0162] In this embodiment, the anti-aging enhanced modified composite particles are prepared by the following method:

[0163] 1) In-situ modification of reduced carbon dots on mesoporous silica using a one-pot hydrothermal method to obtain anti-aging particles:

[0164] 2.8 g of mesoporous silica was added to 200 mL of an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 30 min. Then, 0.7 g of glucose, 0.3 g of oxalic acid, 0.55 g of lutein, and 0.24 g of 3-aminophenylboric acid were added and ultrasonically dispersed for 1 h. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor, reacted at 175 ° C for 8 h, cooled to room temperature, and centrifuged and filtered. The solid product was washed with ethanol and vacuum dried at 55 ° C for 12 h to obtain anti-aging particles.

[0165] 2) Preparation of modified multi-walled carbon nanotubes:

[0166] Take 3 g of multi-walled carbon nanotubes and add them into a mixed acid consisting of 120 mL of 95% by mass concentrated sulfuric acid and 80 mL of 60% by mass concentrated nitric acid, stir and reflux at 80°C for 12 hours, cool to room temperature, centrifuge and filter, wash the solid product with deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain modified multi-walled carbon nanotubes.

[0167] 3) Preparation of modified carbon fiber:

[0168] The micron-sized short-cut carbon fiber was soaked in ethanol for 2 hours, filtered, and dried at 100°C to constant weight to obtain pretreated carbon fiber; 5 g of pretreated carbon fiber was added to 250 mL of a mixed acid solution consisting of 10% by mass hydrogen peroxide and 55% by mass sulfuric acid, ultrasonically dispersed for 30 minutes and then heated to 90°C, treated under a 350 W microwave for 30 minutes, cooled to room temperature and filtered, washed with deionized water until neutral, and dried at 100°C to constant weight to obtain modified carbon fiber.

[0169] 4) Using the metal ion bridging effect, the modified multi-walled carbon nanotubes, anti-aging particles and modified carbon fibers are grafted to prepare composite functional particles:

[0170] 8 g of modified carbon fiber, 3.8 g of anti-aging particles, 1.7 g of modified multi-walled carbon nanotubes, and 3.2 g of Mn(NO3)2 were added to 300 mL of ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 1 hour. The resulting dispersion was transferred to a reactor and reacted at 250°C for 4 hours. After the reaction was completed, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and then vacuum dried at 70°C for 8 hours to obtain composite functional particles.

[0171] 5) Modifying polystyrene on the composite functional particles to obtain polymer modified composite particles, and then immersing them in an antioxidant solution to obtain anti-aging enhanced modified composite particles, the specific steps are:

[0172] 5-1. Wash the styrene monomer three times with a 0.2 mol / L NaOH solution, then wash with deionized water until neutral, and then dry with anhydrous Na2SO4 to obtain purified styrene monomer;

[0173] 5-2. Take 2 g of composite functional particles and 2 mL of silane coupling agent KH-570 and add them to 50 mL of isopropanol. Stir at 65 °C for 2 h, filter, wash the solid product with isopropanol, then add it to 75 mL of purified styrene monomer, stir and disperse for 45 min to obtain a precursor solution.

[0174] 5-3. Take 1.5 g of sodium dodecyl sulfate and add it to 400 mL of deionized water. After stirring for 5 min, add 0.28 g of hexadecanol and stir at 50°C for 10 min to obtain an additive solution.

[0175] 5-4. Add the precursor solution 1 to the auxiliary solution, stir for 30 minutes, then heat to 68°C, drop 0.25g of azobisisobutyronitrile, and react at constant temperature for 5 hours to obtain polymer-modified composite particles;

[0176] 5-5. Add 1 g of polymer modified composite particles to an acetone solution of antioxidant RD at a concentration of 4 mg / mL, first ultrasonicate for 1 h, then soak for 6 h, centrifuge, wash the solid product with ethanol, and vacuum dry at 50°C for 8 h to obtain anti-aging enhanced modified composite particles.

[0177] In this embodiment, the modified epoxy resin composition is prepared by the following method:

[0178] Add 5 g of 2,2'-diaminodiphenyl disulfide to 40 g of ethanol, stir at 50°C for 10 min, then add 24.5 g of bisphenol F epoxy resin and 10.5 g of bis(4-glycidoxy)diphenyl disulfide, stir at 70°C for 30 min, then place in a vacuum oven, degas at 60°C for 30 min, and finally keep warm at 130°C for 4 h, cool to room temperature to obtain a self-healing epoxy resin.

[0179] Example 3

[0180] A high-performance composite sealing gasket and a preparation method thereof, the method comprising the following steps:

[0181] S1. Weigh the following raw materials by weight:

[0182]

[0183]

[0184] According to the above ratio, nitrile rubber, EPDM rubber, anti-aging enhanced modified composite particles, and modified epoxy resin composition were added into an internal mixer, mixed at 75° C. for 5 min, and then talcum powder, zinc oxide, and paraffin were added, the temperature was raised to 82° C., and mixed for 8 min to obtain a mixed rubber material;

[0185] S2. Add the mixed rubber material, sulfur and vulcanization accelerator into an open mixing mill, mix at 70°C for 8 minutes, and discharge the material to obtain a gasket rubber material; S3. Place the gasket rubber material in a mold for compression molding according to the designed size and shape of the sealing gasket to obtain a raw rubber gasket; S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket in a vulcanizer to obtain a sealing gasket; wherein, the first stage vulcanization temperature is 165°C, the vulcanization time is 10 minutes, and the vulcanization pressure is 18MPa; the second stage vulcanization temperature is 155°C, the vulcanization time is 20 minutes, and the vulcanization pressure is 14MPa; and a sealing gasket is obtained.

[0186] In this embodiment, the anti-aging enhanced modified composite particles are prepared by the following method:

[0187] 1) In-situ modification of reduced carbon dots on mesoporous silica using a one-pot hydrothermal method to obtain anti-aging particles:

[0188] 2.2 g of mesoporous silica was added to 200 mL of an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 30 min. Then, 0.7 g of glucose, 0.3 g of oxalic acid, 0.55 g of lutein, and 0.24 g of 3-aminophenylboric acid were added and ultrasonically dispersed for 1 h. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor, reacted at 175 ° C for 8 h, cooled to room temperature, and centrifuged and filtered. The solid product was washed with ethanol and vacuum dried at 55 ° C for 12 h to obtain anti-aging particles.

[0189] 2) Preparation of modified multi-walled carbon nanotubes:

[0190] Take 3 g of multi-walled carbon nanotubes and add them into a mixed acid consisting of 120 mL of 95% by mass concentrated sulfuric acid and 80 mL of 60% by mass concentrated nitric acid, stir and reflux at 80°C for 12 hours, cool to room temperature, centrifuge and filter, wash the solid product with deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain modified multi-walled carbon nanotubes.

[0191] 3) Preparation of modified carbon fiber:

[0192] The micron-sized short-cut carbon fiber was soaked in ethanol for 2 hours, filtered, and dried at 100°C to constant weight to obtain pretreated carbon fiber; 5 g of pretreated carbon fiber was added to 250 mL of a mixed acid solution consisting of 10% by mass hydrogen peroxide and 55% by mass sulfuric acid, ultrasonically dispersed for 30 minutes and then heated to 90°C, treated under a 350 W microwave for 30 minutes, cooled to room temperature and filtered, washed with deionized water until neutral, and dried at 100°C to constant weight to obtain modified carbon fiber.

[0193] 4) Using the metal ion bridging effect, the modified multi-walled carbon nanotubes, anti-aging particles and modified carbon fibers are grafted to prepare composite functional particles:

[0194] 8.5 g of modified carbon fiber, 3.8 g of anti-aging particles, 1.5 g of modified multi-walled carbon nanotubes, and 3.9 g of Mn(NO3)2 were added to 300 mL of ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 1 hour. The resulting dispersion was transferred to a reactor and reacted at 250°C for 4 hours. After the reaction was completed, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and then vacuum dried at 70°C for 8 hours to obtain composite functional particles.

[0195] 5) Modifying polystyrene on the composite functional particles to obtain polymer modified composite particles, and then immersing them in an antioxidant solution to obtain anti-aging enhanced modified composite particles, the specific steps are:

[0196] 5-1. Wash the styrene monomer three times with a 0.2 mol / L NaOH solution, then wash with deionized water until neutral, and then dry with anhydrous Na2SO4 to obtain purified styrene monomer;

[0197] 5-2. Take 2 g of composite functional particles and 2 mL of silane coupling agent KH-570 and add them to 50 mL of isopropanol. Stir at 65 °C for 2 h, filter, wash the solid product with isopropanol, then add it to 75 mL of purified styrene monomer, stir and disperse for 45 min to obtain a precursor solution.

[0198] 5-3. Take 1.5 g of sodium dodecyl sulfate and add it to 400 mL of deionized water. After stirring for 5 min, add 0.28 g of hexadecanol and stir at 50°C for 10 min to obtain an additive solution.

[0199] 5-4. Add the precursor solution 1 to the auxiliary solution, stir for 30 minutes, then heat to 68°C, drop 0.25g of azobisisobutyronitrile, and react at constant temperature for 5 hours to obtain polymer-modified composite particles;

[0200] 5-5. Add 1 g of polymer modified composite particles to an acetone solution of antioxidant RD at a concentration of 4 mg / mL, first ultrasonicate for 1 h, then soak for 6 h, centrifuge, wash the solid product with ethanol, and vacuum dry at 50°C for 8 h to obtain anti-aging enhanced modified composite particles.

[0201] In this embodiment, the modified epoxy resin composition is prepared by the following method:

[0202] 4.2 g of 2,2'-diaminodiphenyl disulfide was added to 40 g of ethanol, stirred at 50°C for 10 min, then 25 g of bisphenol F epoxy resin and 11 g of bis(4-glycidoxy)diphenyl disulfide were added, stirred at 70°C for 30 min, then placed in a vacuum oven, degassed at 60°C for 30 min, and finally kept at 130°C for 4 h, cooled to room temperature, and a self-healing epoxy resin was obtained.

[0203] Example 4

[0204] A high-performance composite sealing gasket and a preparation method thereof, the method comprising the following steps:

[0205] S1. Weigh the following raw materials by weight:

[0206]

[0207]

[0208] According to the above ratio, nitrile rubber, EPDM rubber, anti-aging enhanced modified composite particles, and modified epoxy resin composition were added into an internal mixer, mixed at 75° C. for 5 min, and then talcum powder, zinc oxide, and paraffin were added, the temperature was raised to 82° C., and mixed for 8 min to obtain a mixed rubber material;

[0209] S2. Add the mixed rubber material, sulfur and vulcanization accelerator into an open mixing mill, mix at 70°C for 8 minutes, and discharge the material to obtain a gasket rubber material; S3. Place the gasket rubber material in a mold for compression molding according to the designed size and shape of the sealing gasket to obtain a raw rubber gasket; S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket in a vulcanizer to obtain a sealing gasket; wherein, the first stage vulcanization temperature is 165°C, the vulcanization time is 10 minutes, and the vulcanization pressure is 18MPa; the second stage vulcanization temperature is 155°C, the vulcanization time is 20 minutes, and the vulcanization pressure is 14MPa; and a sealing gasket is obtained.

[0210] In this embodiment, the anti-aging enhanced modified composite particles are prepared by the following method:

[0211] 1) In-situ modification of reduced carbon dots on mesoporous silica using a one-pot hydrothermal method to obtain anti-aging particles:

[0212] 2.5 g of mesoporous silica was added to 200 mL of an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 30 min. Then, 0.7 g of glucose, 0.3 g of oxalic acid, 0.55 g of lutein, and 0.24 g of 3-aminophenylboric acid were added and ultrasonically dispersed for 1 h. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor, reacted at 175 ° C for 8 h, cooled to room temperature, and centrifuged and filtered. The solid product was washed with ethanol and vacuum dried at 55 ° C for 12 h to obtain anti-aging particles.

[0213] 2) Preparation of modified multi-walled carbon nanotubes:

[0214] Take 3 g of multi-walled carbon nanotubes and add them into a mixed acid consisting of 120 mL of 95% by mass concentrated sulfuric acid and 80 mL of 60% by mass concentrated nitric acid, stir and reflux at 80°C for 12 hours, cool to room temperature, centrifuge and filter, wash the solid product with deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain modified multi-walled carbon nanotubes.

[0215] 3) Preparation of modified carbon fiber:

[0216] The micron-sized short-cut carbon fiber was soaked in ethanol for 2 hours, filtered, and dried at 100°C to constant weight to obtain pretreated carbon fiber; 5 g of pretreated carbon fiber was added to 250 mL of a mixed acid solution consisting of 10% by mass hydrogen peroxide and 55% by mass sulfuric acid, ultrasonically dispersed for 30 minutes and then heated to 90°C, treated under a 350 W microwave for 30 minutes, cooled to room temperature and filtered, washed with deionized water until neutral, and dried at 100°C to constant weight to obtain modified carbon fiber.

[0217] 4) Using the metal ion bridging effect, the modified multi-walled carbon nanotubes, anti-aging particles and modified carbon fibers are grafted to prepare composite functional particles:

[0218] 8 g of modified carbon fiber, 3.8 g of anti-aging particles, 1.5 g of modified multi-walled carbon nanotubes, and 3.58 g of Mn(NO3)2 were added to 300 mL of ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 1 hour. The resulting dispersion was transferred to a reactor and reacted at 250°C for 4 hours. After the reaction was completed, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and then vacuum dried at 70°C for 8 hours to obtain composite functional particles.

[0219] 5) Modifying polystyrene on the composite functional particles to obtain polymer modified composite particles, and then immersing them in an antioxidant solution to obtain anti-aging enhanced modified composite particles, the specific steps are:

[0220] 5-1. Wash the styrene monomer three times with a 0.2 mol / L NaOH solution, then wash with deionized water until neutral, and then dry with anhydrous Na2SO4 to obtain purified styrene monomer;

[0221] 5-2. Take 2 g of composite functional particles and 2 mL of silane coupling agent KH-570 and add them to 50 mL of isopropanol. Stir at 65 °C for 2 h, filter, wash the solid product with isopropanol, then add it to 75 mL of purified styrene monomer, stir and disperse for 45 min to obtain a precursor solution.

[0222] 5-3. Take 1.5 g of sodium dodecyl sulfate and add it to 400 mL of deionized water. After stirring for 5 min, add 0.28 g of hexadecanol and stir at 50°C for 10 min to obtain an additive solution.

[0223] 5-4. Add the precursor solution 1 to the auxiliary solution, stir for 30 minutes, then heat to 68°C, drop 0.25g of azobisisobutyronitrile, and react at constant temperature for 5 hours to obtain polymer-modified composite particles;

[0224] 5-5. Add 1 g of polymer modified composite particles to an acetone solution of antioxidant RD at a concentration of 4 mg / mL, first ultrasonicate for 1 h, then soak for 6 h, centrifuge, wash the solid product with ethanol, and vacuum dry at 50°C for 8 h to obtain anti-aging enhanced modified composite particles.

[0225] In this embodiment, the modified epoxy resin composition is prepared by the following method:

[0226] 4.5 g of 2,2'-diaminodiphenyl disulfide was added to 40 g of ethanol, stirred at 50°C for 10 min, then 25 g of bisphenol F epoxy resin and 10 g of bis(4-epoxypropoxy)diphenyl disulfide were added, stirred at 70°C for 30 min, then placed in a vacuum oven, degassed at 60°C for 30 min, and finally kept at 130°C for 4 h, cooled to room temperature, and a self-healing epoxy resin was obtained.

[0227] Comparative Example 1

[0228] A high-performance composite sealing gasket and a preparation method thereof, the method comprising the following steps:

[0229] S1. Weigh the following raw materials by weight:

[0230]

[0231]

[0232] According to the above ratio, nitrile rubber, EPDM rubber, anti-aging enhanced modified composite particles, and modified epoxy resin composition were added to an internal mixer, mixed at 75°C for 5 minutes, and then talcum powder, zinc oxide, paraffin, and antioxidant RD were added, the temperature was raised to 82°C, and mixed for 8 minutes to obtain a mixed rubber material;

[0233] S2. Add the mixed rubber material, sulfur and vulcanization accelerator into an open mixing mill, mix at 70°C for 8 minutes, and discharge the material to obtain a gasket rubber material; S3. Place the gasket rubber material in a mold for compression molding according to the designed size and shape of the sealing gasket to obtain a raw rubber gasket; S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket in a vulcanizer to obtain a sealing gasket; wherein, the first stage vulcanization temperature is 165°C, the vulcanization time is 10 minutes, and the vulcanization pressure is 18MPa; the second stage vulcanization temperature is 155°C, the vulcanization time is 20 minutes, and the vulcanization pressure is 14MPa; and a sealing gasket is obtained.

[0234] Comparative Example 2

[0235] This example is basically the same as Example 4, except that bisphenol F epoxy resin is used instead of the modified epoxy resin composition in Example 4.

[0236] Comparative Example 3

[0237] This example is basically the same as Example 4, and the main differences are listed below: In this example, the anti-aging enhanced modified composite particles are prepared by the following method:

[0238] 1) preparing modified multi-walled carbon nanotubes, the same as in Example 4;

[0239] 2) preparing modified carbon fiber, the same as in Example 4;

[0240] 3) Using the metal ion bridging effect, modified multi-walled carbon nanotubes, mesoporous silica and modified carbon fibers are grafted to prepare composite functional particles:

[0241] 8 g of modified carbon fiber, 3.8 g of mesoporous silica, 1.5 g of modified multi-walled carbon nanotubes, and 3.58 g of Mn(NO3)2 were added to 300 mL of ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 1 hour. The resulting dispersion was transferred to a reactor and reacted at 250°C for 4 hours. After the reaction was completed, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and then vacuum dried at 70°C for 8 hours to obtain composite functional particles.

[0242] 4) Modifying polystyrene on the composite functional particles to obtain polymer modified composite particles, and then immersing them in an antioxidant solution to obtain anti-aging enhanced modified composite particles, which is the same as Example 4.

[0243] Comparative Example 4

[0244] S1. Weigh the following raw materials by weight:

[0245]

[0246] According to the above ratio, nitrile rubber, EPDM rubber, anti-aging particles, modified multi-walled carbon nanotubes, modified carbon fibers, and modified epoxy resin composition were added to an internal mixer, mixed at 75° C. for 5 min, and then talcum powder, zinc oxide, paraffin, and antioxidant RD were added, the temperature was raised to 82° C., and mixed for 8 min to obtain a mixed rubber material;

[0247] S2. Add the mixed rubber material, sulfur and vulcanization accelerator into an open mixing mill, mix at 70°C for 8 minutes, and discharge the material to obtain a gasket rubber material; S3. Place the gasket rubber material in a mold for compression molding according to the designed size and shape of the sealing gasket to obtain a raw rubber gasket; S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket in a vulcanizer to obtain a sealing gasket; wherein, the first stage vulcanization temperature is 165°C, the vulcanization time is 10 minutes, and the vulcanization pressure is 18MPa; the second stage vulcanization temperature is 155°C, the vulcanization time is 20 minutes, and the vulcanization pressure is 14MPa; and a sealing gasket is obtained.

[0248] Among them, the preparation methods of the anti-aging particles, modified multi-walled carbon nanotubes, and modified carbon fibers are the same as those in Example 4.

[0249] Comparative Example 5

[0250] This example is basically the same as Example 4, except that in this example, the anti-aging enhanced modified composite particles are prepared by the following method:

[0251] 1. Prepare composite functional particles, the same as steps 1) to 4) of Example 4;

[0252] 2. Add 1 g of composite functional particles to an acetone solution of antioxidant RD with a concentration of 4 mg / mL, first ultrasonicate for 1 h, then soak for 6 h, centrifuge, wash the solid product with ethanol, and vacuum dry at 50°C for 8 h to obtain anti-aging enhanced modified composite particles.

[0253] Comparative Example 6

[0254] A high-performance composite sealing gasket and a preparation method thereof, the method comprising the following steps:

[0255] S1. Weigh the following raw materials by weight:

[0256]

[0257] According to the above ratio, nitrile rubber, EPDM rubber, anti-aging enhanced modified composite particles, and modified epoxy resin composition were added to an internal mixer, mixed at 75°C for 5 minutes, and then talcum powder, zinc oxide, paraffin, and antioxidant RD were added, the temperature was raised to 82°C, and mixed for 8 minutes to obtain a mixed rubber material;

[0258] S2. Add the mixed rubber material, sulfur and vulcanization accelerator into an open mixing mill, mix at 70°C for 8 minutes, and discharge the material to obtain a gasket rubber material; S3. Place the gasket rubber material in a mold for compression molding according to the designed size and shape of the sealing gasket to obtain a raw rubber gasket; S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket in a vulcanizer to obtain a sealing gasket; wherein, the first stage vulcanization temperature is 165°C, the vulcanization time is 10 minutes, and the vulcanization pressure is 18MPa; the second stage vulcanization temperature is 155°C, the vulcanization time is 20 minutes, and the vulcanization pressure is 14MPa; and a sealing gasket is obtained.

[0259] In this example, the anti-aging enhanced modified composite particles were prepared by the following method:

[0260] 1. Prepare composite functional particles, the same as steps 1) to 4) of Example 4;

[0261] 2. Modify polystyrene on the composite functional particles to obtain polymer modified composite particles. The specific steps are as follows:

[0262] 2-1. Wash the styrene monomer three times with a 0.2 mol / L NaOH solution, then wash with deionized water until neutral, and then dry with anhydrous Na2SO4 to obtain purified styrene monomer;

[0263] 2-2. Take 2 g of composite functional particles and 2 mL of silane coupling agent KH-570 and add them to 50 mL of isopropanol. Stir at 65 °C for 2 h, filter, wash the solid product with isopropanol, then add it to 75 mL of purified styrene monomer, stir and disperse for 45 min to obtain a precursor solution.

[0264] 2-3. Take 1.5 g of sodium dodecyl sulfate and add it to 400 mL of deionized water. After stirring for 5 min, add 0.28 g of hexadecanol and stir at 50 ° C for 10 min to obtain an additive solution.

[0265] 2-4. Add the precursor solution 1 to the auxiliary solution, stir for 30 minutes, then heat to 68° C., drop 0.25 g of azobisisobutyronitrile, and react at a constant temperature for 5 hours to obtain anti-aging enhanced modified composite particles.

[0266] 1. Performance Characterization:

[0267] Taking Example 4 as an example, the following performance characterization tests were performed:

[0268] 1. Reference Figure 1, is the infrared absorption spectrum of the anti-aging particles (SiO2@RCDs) prepared in Example 4. From the test results, it can be seen that the anti-aging particles have abundant functional groups such as -CH, -NH, CO, -OH, -C=O, BC, etc.

[0269] 2. Antioxidant properties of anti-aging particles

[0270] The anti-aging particles (SiO2@RCDs) prepared in Example 4 were prepared into an anti-aging particle dispersion with a concentration of 1 mg / mL using deionized water, and a nitrogen free radical (DPPH) scavenging ability test kit (DPPH-A001-96T, Shanghai Huicheng Biotechnology Co., Ltd.) was used to detect the antioxidant properties of the anti-aging particle dispersion over a certain period of time.

[0271] Principle of determination: DPPH free radical is a relatively stable nitrogen-containing free radical with a single electron and strong absorption at 517nm. If other substances provide an electron to pair this single electron, its absorption will disappear and fade, and the degree of fading is proportional to the amount of electrons accepted. That is, the ability of the reactant to remove nitrogen free radicals is inversely proportional to the absorbance of the reagent at 517nm; that is, the lower the absorbance at 517nm, the more nitrogen free radicals are removed, and the stronger the corresponding antioxidant performance.

[0272] Test results such as Figure 2 As shown, from Figure 2 It can be seen that the anti-aging particles exhibit a longer-lasting antioxidant capacity.

[0273] 3. Anti-aging enhanced sustained release performance of modified composite particles (PS@SiO2@RCDs-CF-CNTs@RD);

[0274] 1 g of the anti-aging enhanced modified composite particles prepared in Example 4 was placed in 10 mL of acetone and allowed to stand at room temperature. The acetone solution was taken out at regular intervals, and the concentration of the anti-aging RD in the acetone solution was measured by a UV-visible spectrophotometer, and then new acetone solution was added; this was repeated for a certain period of time, and the release percentage of the anti-aging RD at different times was calculated, and a release curve was drawn, as shown in FIG. Figure 3 As shown. The initial content of anti-aging RD in the anti-aging enhanced modified composite particles is calculated by the following method: in step S5-5 of the preparation process, the concentration of the antioxidant RD in the acetone solution of the antioxidant RD after immersion treatment is detected, and the loading amount of the anti-aging RD in the anti-aging enhanced modified composite particles per unit mass can be converted, thereby calculating the initial content of the anti-aging RD in 1g of the anti-aging enhanced modified composite particles prepared in Example 4.

[0275] Test results such as Figure 3As shown, it can be seen from the test results that the anti-aging enhanced modified composite particles can continuously release the anti-aging RD and have a good sustained-release effect.

[0276] 2. Performance test:

[0277] 1. Tensile strength

[0278] Referring to the standard "GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", dumbbell-shaped test strips were first prepared according to the formulation and process of the sealing gasket in the embodiment and the comparative example (i.e., dumbbell-shaped test strips were formed in step S3, and the rest were the same as the preparation process of the sealing gasket), and then the tensile strength was measured using a tensile testing machine. The test results are shown in Table 1 and Figure 4 As shown:

[0279] Table 1

[0280]

[0281] It can be seen from the test results that Examples 1-4 have higher tensile strength; in Comparative Example 1, the tensile strength decreases most significantly due to the lack of addition of anti-aging enhanced modified composite particles; in Comparative Example 3, a network structure is not formed in the anti-aging enhanced modified composite particles, and the tensile strength also decreases significantly; in Comparative Example 5, no polystyrene film is coated, which affects the dispersibility of inorganic substances such as modified carbon fibers and modified multi-walled carbon nanotubes, and the tensile strength also decreases to a certain extent.

[0282] 2. Rebound rate

[0283] The sealing gaskets prepared in the examples and comparative examples were tested according to GB / T20671 "Non-metallic gasket material classification system and test methods Gasket material compression rate and rebound rate test methods". The test results are shown in Table 2 and Figure 5 shown.

[0284] Table 2

[0285]

[0286] 3. Self-healing performance

[0287] Referring to the standard "GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", dumbbell-shaped test strips were first prepared according to the formula and process of the sealing gasket in the embodiment and the comparative example (that is, dumbbell-shaped test strips were formed in step S3, and the rest were the same as the preparation process of the sealing gasket), and then completely cut at the middle position, and then completely aligned, and self-repaired under corresponding conditions. Each group was tested 5 times, and the average self-repair rate was calculated. The calculation formula of the self-repair rate η is:

[0288] σ0 represents the original tensile strength (MPa), σ h It indicates the tensile strength after repair (MPa).

[0289] 3-1. Self-repair at room temperature

[0290] Test the self-repair rate at 25℃ and 2h treatment

[0291] The test results are shown in Table 3 and Figure 6 As shown:

[0292] Table 3

[0293]

[0294] 3-2. Self-repair rate after treatment at 120℃ for 2h

[0295] The test results are shown in Table 4 and Figure 7 As shown:

[0296] Table 4

[0297]

[0298] It can be seen from the test results that the sealing gasket materials prepared in Examples 1-4 have good room temperature self-healing properties, and the self-healing ability is significantly enhanced at high temperature (120° C.); while the self-healing ability of the comparative examples has decreased to varying degrees.

[0299] 4. Sealing performance

[0300] The sealing gaskets prepared in the examples and comparative examples were tested according to GB / T20671 "Classification system and test methods for non-metallic gasket materials and test methods for sealing properties of gasket materials". The test results are shown in Tables 5 and Figure 8 shown.

[0301] Table 5

[0302]

[0303] 5. Aging resistance

[0304] Dumbbell-shaped specimens were prepared in the same manner as in 1, and the tensile strength before aging was recorded as T0;

[0305] Aging treatment was carried out according to the relevant method in standard GB / T3512-2001, the aging temperature was 175°C, and the aging time was 120h. After the aging treatment was completed, the tensile strength after aging was tested and recorded as T1; the tensile strength test method was also the same as 1;

[0306] The tensile strength retention rate S is calculated according to the following formula: S = T1 / T0*100%.

[0307] The test results are shown in Table 6 and Fig. 9 As shown:

[0308] Table 6

[0309]

[0310] It can be seen from the test results that Examples 1-4 have good heat aging resistance, while the comparative examples show varying degrees of decline.

[0311] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a high-performance composite sealing gasket, characterized in that: The following steps are involved: S1, adding nitrile rubber, EPDM rubber, anti-aging enhanced modified composite particles, and modified epoxy resin composition into an internal mixer, mixing under heating, and then adding talcum powder, zinc oxide, and paraffin, heating, mixing, and obtaining a mixed rubber material; S2, adding the mixed rubber material, sulfur and vulcanization accelerator into an open mill, mixing and discharging to obtain a gasket rubber material; S3, molding the gasket rubber material to obtain a raw rubber gasket; S4, using a two-stage vulcanization process to vulcanize the raw rubber gasket to obtain a sealing gasket; The anti-aging enhanced modified composite particles are prepared by the following method: 1) A one-pot hydrothermal method was used to in situ modify reduced carbon dots on mesoporous silica to obtain anti-aging particles; 2) Preparation of modified multi-walled carbon nanotubes; 3) Preparation of modified carbon fiber; 4) Grafting the modified multi-walled carbon nanotubes, anti-aging particles and modified carbon fibers to prepare composite functional particles; 5) Modifying polystyrene on the composite functional particles to obtain polymer modified composite particles, and then immersing them in an antioxidant solution to obtain anti-aging enhanced modified composite particles; Step 1) is as follows: 1.25-5.0 g of mesoporous silica is added to 100-400 mL of an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 15-60 min, and then 0.35-1.4 g of glucose, 0.15-0.6 g of oxalic acid, 0.25-1.1 g of lutein, and 0.12-0.48 g of 3-aminophenylboronic acid are added, and ultrasonically dispersed for 0.5-2 h. The resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 165-190° C. for 4-12 h, cooled to room temperature, and then centrifuged and filtered, the solid product is washed with ethanol, and vacuum dried at 50-70° C. for 6-24 h to obtain anti-aging particles; Step 2) is as follows: 1.5-6 g of multi-walled carbon nanotubes are added to a mixed acid consisting of 60-240 mL of 95% by mass concentrated sulfuric acid and 80 mL of 60% by mass concentrated nitric acid, stirred and refluxed at 70-90° C. for 6-24 h, cooled to room temperature, centrifuged and filtered, the solid product is washed with deionized water until neutral, and vacuum dried at 50-65° C. for 6-24 h to obtain modified multi-walled carbon nanotubes; Step 3) is as follows: The carbon fiber is added to ethanol and soaked for 1-4 hours, filtered, and dried at 90-110°C to constant weight to obtain pretreated carbon fiber; 2.5-10g of the pretreated carbon fiber is added to 125-500mL of a mixed acid solution consisting of 15% by mass hydrogen peroxide and 55% by mass sulfuric acid, ultrasonically dispersed for 15-60min, heated to 80-95°C, treated under a 300-400W microwave for 15-45min, cooled to room temperature, filtered, washed with deionized water until neutral, and dried at 90-110°C to constant weight to obtain modified carbon fiber; Among them, the carbon fiber is micron-sized short-cut carbon fiber with a length of 50 to 400 μm; Step 4) is as follows: 4-16g of modified carbon fiber, 1.9-7.6g of anti-aging particles, 0.75-3.0g of modified multi-walled carbon nanotubes, and 2.0-8.5g of Mn(NO3)2 are added to 150-600mL of an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, and ultrasonically dispersed for 0.5-2h. The obtained dispersion is transferred to a reactor and reacted at 220-280°C for 2-8h. After the reaction is completed, it is cooled to room temperature, centrifuged and filtered, the solid product is washed with deionized water, and then vacuum dried at 60-80°C for 4-12h to obtain composite functional particles; Step 5) is as follows: 5-1. Wash the styrene monomer 2-6 times with a 0.1-0.4 mol / L NaOH solution, then wash with deionized water until neutral, and then dry with anhydrous Na2SO4 to obtain purified styrene monomer; 5-2. Take 1-4g of composite functional particles and 0.1-0.4mL of silane coupling agent KH-570 and add them to 25-100mL of isopropanol, stir at 50-75°C for 1-4h, filter, wash the solid product with isopropanol, then add it to 35-150mL of purified styrene monomer, stir and disperse for 30-90min to obtain a precursor solution; 5-3. Take 0.75-3.0g of sodium dodecyl sulfate and add it to 200-400mL of deionized water. After stirring for 2-15min, add 0.14-0.56g of hexadecanol and stir at 40-60°C for 5-30min to obtain an additive solution. 5-4. Add the precursor liquid to the auxiliary liquid, stir for 15-60 minutes, then heat to 62-73°C, drop 0.25-1.2g of azobisisobutyronitrile, and react at constant temperature for 2.5-8 hours to obtain polymer-modified composite particles; 5-5. Add 0.5-2 g of polymer modified composite particles to an antioxidant solution with a concentration of 1-10 mg / mL, first ultrasonicate for 0.5-2 h, then soak for 3-10 h, centrifuge, wash the solid product with ethanol, and vacuum dry at 40-60° C. for 4-12 h to obtain anti-aging enhanced modified composite particles; The antioxidant solution is prepared by adding any one of antioxidant D, antioxidant RD, antioxidant 124, and antioxidant MB into acetone; The modified epoxy resin composition is prepared by the following method: Add 2.25-9 g of 2,2'-diaminodiphenyl disulfide to 20-80 g of ethanol, stir at 40-55°C for 5-30 min, then add 12.5-50 g of bisphenol F epoxy resin and 5-20 g of bis(4-epoxypropoxy)diphenyl disulfide, stir at 60-80°C for 15-60 min, then place in a vacuum oven, degas at 50-65°C for 15-60 min, finally keep warm at 120-140°C for 2-6 h, cool to room temperature, and obtain a self-healing epoxy resin.

2. The method for preparing a high-performance composite sealing gasket according to claim 1, characterized in that: The following steps are involved: S1. By weight, 100 parts of nitrile rubber, 13.5-54 parts of EPDM rubber, 7-28 parts of anti-aging enhanced modified composite particles, and 15.5-42 parts of modified epoxy resin composition are added to an internal mixer, mixed at 60-78° C. for 2-15 min, and then 4.5-19 parts of talc, 0.6-2.4 parts of zinc oxide, and 1.5-6 parts of paraffin are added, the temperature is raised to 80-85° C., and mixed for 4-16 min to obtain a mixed rubber material; S2, adding 0.35-1.4 parts by weight of sulfur, 0.9-3.6 parts by weight of vulcanization accelerator and the mixed rubber material obtained in step S1 into an open mill, mixing at 65-75° C. for 4-15 minutes, and discharging to obtain a gasket rubber material; S3, placing the gasket rubber material in a mold for compression molding according to the designed size and shape of the sealing gasket to obtain a raw rubber gasket; S4. Use a two-stage vulcanization process to vulcanize the raw rubber gasket in a vulcanizer to obtain a sealing gasket; wherein, the first stage vulcanization temperature is 160-175°C, the vulcanization time is 5-15min, and the vulcanization pressure is 12-20MPa; the second stage vulcanization temperature is 150-160°C, the vulcanization time is 10-30min, and the vulcanization pressure is 5-15MPa.

3. A high-performance composite sealing gasket, characterized in that: It is prepared by the method according to any one of claims 1 to 2.

Citation Information

Patent Citations

  • A puncture-resistant rubber material and sealing gasket

    CN113429687B

  • Oil-resistant rubber gasket, preparation method and high-strength oil-resistant rubber expansion joint

    CN115558175A

  • Polytetrafluoroethylene sealing gaskets and their preparation methods

    CN116731458B

  • Processing technology of rubber sealing ring

    CN113527774A